Urgensi dan Strategi Analisis Pekerjaan dalam Pengelolaan SDM Pendidikan Islam di Indonesia - Ahmad Sabiq Muizzudin; Sukarman Sukarman; Muh. Arif Jalaluddin Zuhri (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
This article discusses the importance of job analysis as a fundamental component of human resource management (HRM) within Islamic educational institutions in Indonesia. Using a qualitative approach based on a literature review, the study highlights the strategic role of job analysis in developing job descriptions, job specifications, and the professional development of human resources. Job analysis serves not only as an administrative tool but also contributes to institutional efficiency, the enhancement of educational quality, and the readiness of institutions to face global challenges and technological advancements. By systematically identifying and evaluating job roles and responsibilities, institutions can align their HR practices with organizational goals and the evolving demands of the educational sector. The application of analytical models such as the Position Analysis Questionnaire (PAQ), Functional Job Analysis (FJA), and the Job Characteristics Model ensures that job analysis is comprehensive and tailored to the specific needs of the institution. The article emphasizes that a results-oriented approach is more relevant for modern educational institutions, particularly those within Islamic settings. The findings indicate that the optimal implementation of job analysis can strengthen the governance of Islamic educational institutions, enhance their operational effectiveness, and improve the competitiveness of their human resources in the global education landscapes.